Design and Implementation of an Interactive Science Educational Game to Improve Science Literacy of Elementary Students in Grades 3–6 - Eldo, Handry; Najmi, Muazziss (Gameology and Multimedia Expert, 2025)
Interactive educational games are one of the innovative approaches to improving science literacy skills among elementary school students. This study aims to design and implement an interactive science-based educational game to help students in grades 3–6 understand scientific concepts in a fun and engaging way. The research methods include user needs analysis, game concept design, software development, and evaluation to measure effectiveness and user responses. The game was designed by referring to the current science curriculum and integrating educational elements that suit children's developmental stages. The development of this game uses two programming languages, namely CSS (Cascading Style Sheets) and JavaScript (JS), to control the appearance and interactions on the web platform. The result of this study is an interactive educational web-based game that offers various challenges and learning activities that are both entertaining and educational. Initial evaluations show positive responses from users, both in terms of enjoyment and improved understanding of the science material presented. In conclusion, this interactive educational game has great potential as an additional learning tool to support science teaching in elementary schools. Further development and integration into the curriculum are expected to significantly improve children's science literacy.